More accounting changes : financial reporting through the age of crisis and globalization - Herz, Robert H. (Emerald Group Publishing Limited, 2016)
This volume, More Accounting Changes, is a revised and updated edition of Herz's earlier work, reflecting: developments in financial reporting (including those relating to international convergence of accounting standards); global developments regarding the use of International Financial Reporting Standards; current efforts at disclosure modernization and simplification by the SEC and FASB; a discussion of whether the U.S. is falling behind in corporate reporting ; the rise of 'Integrated Reporting'; the work of the Sustainability Accounting Standards Board (chaired by Michael Bloomberg); and recent regulatory developments emanating from the financial crisis and their interrelationship with financial reporting.